Selecting Suitable Sites for Wind Energy Harvesting in Iraq using GIS Techniques - Nassif, Wedyan G.; Elhmaidi, Dalila; Al-Timimi, Yaseen K. (Iraqi Journal of Science, 2024)
Wind energy harnesses the kinetic force of the wind through turbines to produce electricity. As a critical renewable energy source, it presents a sustainable alternative to fossil fuels. The availability of wind energy is geographically contingent. This paper aims to pinpoint optimal sites for wind energy development in Iraq and to secure future energy needs from renewable sources to achieve this, a multi-criteria analysis utilizing Geographic Information Systems (GIS) was employed to determine the prime locations for wind energy extraction. Vital climatic data incorporated into this analysis included a RASTER file of the study area’s annual wind speed, temperature, precipitation, soil moisture, and NDVI (Normalized Difference Vegetation Index) roads, urban centers, terrain gradients, and land utilization patterns were instrumental in constructing a GIS-based model. This model harnessed the weighted overlay tool within ArcGIS 10.7.1’s Spatial Analysis Tools to classify and integrate various raster datasets. Findings reveal that the most favorable locations for wind energy exploitation are in Iraq’s southeastern sectors. These zones are not only marked by vigorous winds averaging speeds over 6.2 meters per second but also benefit from their proximity to power grids, accessible roads, and gentle slopes, making them prime candidates for wind farm installation. The research also notes that regions with a high suitability index for wind energy development constitute 5.3% of the total examined area. This is a robust indicator of Iraq’s capacity for wind energy utilization. Meanwhile, 79.7% of the territory received a moderate suitability rating, 9.5% was categorized as poorly suitable, and 5.4% was considered unsuitable for wind energy projects. These insights underscore the significant potential for harvesting wind energy in Iraq and guide strategic planning for its implementation.